Smartphones as locative media - Frith, Jordan (Cambridge, UK Polity, 2015)
"Smartphone adoption has surpassed 50% of the population in more than 15 countries, and there are now more than one million mobile applications people can download to their phones. Many of these applications take advantage of smartphones as locative media, which is what allows smartphones to be located in physical space. Applications that take advantage of people's location are called location-based services, and they are the focus of this book.Smartphones as locative media raise important questions about how we understand the complicated relationship between the Internet and physical space. This book addresses these questions through an interdisciplinary theoretical framework and a detailed analysis of how various popular mobile applications including Google Maps, Facebook, Instagram, Yelp, and Foursquare use people's location to provide information about their surrounding space.The topics explored in this book are essential reading for anyone interested in how smartphones and location-based services have begun to impact the ways we navigate and engage with the physical world"-- Provided by publisher.
Machine generated contents note: Acknowledgments Chapter 1: From atoms to bits and back again Chapter 2: Mobilities and the spatial turn Chapter 3: The infrastructure of locative media Chapter 4: Wayfinding through mobile interfaces Chapter 5: Location and social networks Chapter 6: Writing and archiving space Chapter 7: Market forces and the shaping of location-based services Chapter 8: The negotiation of locational privacy Conclusion: The future of locative media Notes References.
Includes bibliographical references and index.
Keywords: Location-based services; Mobile computing; Smartphones; Location-based services -- Social aspects; Mobile computing -- Social aspects